Haemophilia and ageing. (28th December 2018) - Shapiro, Susan; Makris, Mike
Summary: Advances in the development of effective and safe treatments for haemophilia over the last 50 years have resulted in a significant increase in the life expectancy of persons with haemophilia (PWH). The management of this new cohort of middle‐aged and elderly PWH is challenging because of the opposing risks of haemophilia and age‐related cardiovascular disease and malignancy. Furthermore, this cohort of ageing PWH has the additional comorbidities of human immunodeficiency virus/hepatitis C and chronic haemophilic arthropathy. This article reviews the prevalence, underlying mechanisms and treatment strategies for managing these comorbidities. International collaboration is essential for registry data and further prospective trials to inform optimal evidence‐based management for this rare disorder in the future.